القراءة البراغماتية للنظريات التربوية الكلاسيكية من خلال الفيلسوف "جون ديوي - البار, عبد الحفيظ (جامعة الوادي - University of Eloued, 2015)
إن المعالم التّربوية الجديدة التي رسم "جون ديوي" ملامحها، بعد ثورته على المفاهيم التربوية التقليدية، حينما غيّر مركز بناء القضايا التعليمية من المادة المعرفية إلى المتعلم ذاته بكل ما يملكه من مواهب وميولات، وانتهى به المقام إلى بلورة ما يعرف بالتربية التقدمية التي شكلت بمناهجها وأهدافها ضرورة ملحة وغاية منشودة لكل اصلاح تربوي في القرن العشرين، ليست إلا ثمرة اطلاعه على أهم النظريات التربوية التي قدمها الباحثون عبر التاريخ. "جون ديوي" الفيلسوف البراغماتي، بدأ حياته الفكرية شغوفا بقراءة ما كُتب في التربية، وتوجه إليها بالتحليل، بالنقد تارة وبالتثمين تارة أخرى، وأستفاد من محاسنها وتجاوز مساوئها، وأراد من ذلك أن يبني تصورا جديدا للتربية يتماشى والتقدم الحاصل في الحياة، ويساير طبيعة المجتمع الأمريكي وثقافته. Abstract: The new educational attractions that draw "John Dewy" features, after the revolution to the traditional educational concepts, when it is the center of the construction of educational issues of material knowledge to himself learner, and crystallized what is known as progressive education that shaped their curricula and objectives is an urgent necessity for every reform education in the twentieth century, It is not only the result of studying the most important educational theories throughout history. Intellectual life began to read what has been written in education and went to the analysis, criticism and valuation in, and benefited from their advantages and bypass the disadvantages, and wanted it to build a new vision of education in line with the progress in life, and the faddish nature of American society and culture.
مقال
Keywords: الفلسفة البراغماتية، فلسفة التربية البراغماتية، النظرية التربوية، التربية التقدمية، الخبرة التربوية; philosophy of pragmatism, the philosophy of pragmatism education, educational theory, progressive education, educational experience